(untitled) (PANGEEA, 2025)
ABSTRACT: Way of organizing, planning and optimization of agricultural space. History, and more so this showed us that the organization of agricultural space and technical means have become apparent or real areas unfit for agriculture in plantations and intensive crops, such as incompetence, indifference, desire to win could degrade or leave particularly fallow fertile soils. Moreover, the rational use of land by harmonizing with the natural conditions and socio-economic development requirements of organization and planning techniques takes specific issues around the various stages of development. Keywords: organization of agricultural space, harmonizing with the natural conditions.